2018
DOI: 10.1177/0306624x18794135
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Interests of Child Sexual Exploitation Material (CSEM) Consumers: Four Patterns of Severity Over Time

Abstract: This study analyzed the evolution over time of the activity of consumers of child sexual exploitation material (CSEM). To this end, images and metadata were extracted from the hard drives of 40 individuals convicted of possession of child pornography and analyzed. A sample of these images ( N = 61,244) was categorized by the age of the subjects depicted and-using the Combating Paedophile Information Networks in Europe (COPINE) scale-by severity of the acts depicted. Collecting activity was observed to follow f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 37 publications
4
19
0
1
Order By: Relevance
“…They found that participants (undergraduate students) exposed to barely legal pornography were more likely to make cognitive associations between children and sexuality than participants shown adult pornography. Despite the limited research base, the available findings are consistent with theoretical models that portray involvement in CSEM use as becoming progressively more problematic over time through an iterative process of habituation and escalation (e.g., Fortin & Proulx, 2019; Paul & Linz, 2008; Quayle & Taylor, 2004).…”
Section: Introductionsupporting
confidence: 70%
“…They found that participants (undergraduate students) exposed to barely legal pornography were more likely to make cognitive associations between children and sexuality than participants shown adult pornography. Despite the limited research base, the available findings are consistent with theoretical models that portray involvement in CSEM use as becoming progressively more problematic over time through an iterative process of habituation and escalation (e.g., Fortin & Proulx, 2019; Paul & Linz, 2008; Quayle & Taylor, 2004).…”
Section: Introductionsupporting
confidence: 70%
“…As such, crime scripting of Darkweb CSEM fora can constitute an important first step toward a more detailed analysis of the various dimensions of members' online behaviors and the underlying communication network, its structure, strengths, and weaknesses by applying methods of longitudinal data analysis (Fortin & Proulx, 2019) and mathematical concepts and techniques from social network analysis (Morselli & Roy, 2008;Tompson & Chainey, 2011). Recently, one such social network analysis was conducted, using one of the data sets that was also used in this study to explore forum structures and identify key players, (Fonhof et al, 2019).…”
Section: Research Implicationsmentioning
confidence: 99%
“…Temporal patterns of CSEM consumption were examined by Fortin and Proulx (2019) through images and metadata extracted from the hard-drives of 40 people convicted of CSEM possession. A sample of 61,244 images was categorized by the age of the children in the images and the severity of the victimisation using the COPINE 10-point scale (Taylor et al 2001) which ranges from 1 = non-erotic and non-sexualized pictures to 10 = sadistic/bestiality images involving children.…”
mentioning
confidence: 99%